Anna's Heaven - Hole, Stian; Bartlett, Don (Grand Rapids Michigan : Eerdmans Books for Young Readers, 2014)
After the death of her mother, Anna and her father imagine that Heaven might be a place where one can help in God's garden, visit with old friends, and take off one's socks whenever one pleases.
Keywords: Heaven -- Juvenile fiction; Future life -- Juvenile fiction; Fathers and daughters -- Juvenile fiction; Death -- Juvenile fiction; Imagination -- Juvenile fiction; Heaven -- Fiction; Future life -- Fiction; Fathers and daughters -- Fiction; Death -- Fiction; Imagination -- Fiction